2019
DOI: 10.1093/mnras/stz2158
|View full text |Cite
|
Sign up to set email alerts
|

NuGrid stellar data set – III. Updated low-mass AGB models and s-process nucleosynthesis with metallicities Z= 0.01, Z = 0.02, and Z = 0.03

Abstract: The production of the neutron-capture isotopes beyond iron that we observe today in the Solar system is the result of the combined contribution of the r-process, the s-process, and possibly the i-process. Low-mass asymptotic giant branch (AGB) (1.5 < M/M⊙ < 3) and massive (M > 10 M⊙) stars have been identified as the main site of the s-process. In this work we consider the evolution and nucleosynthesis of low-mass AGB stars. We provide an update of the NuGrid Set models, adopting the same general phys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 54 publications
1
87
1
Order By: Relevance
“…We re-computed the s-process nucleosynthesis for stellar models of 2 and 3M adopting our new evaluations for 22 Ne(α,n) 25 Mg and 22 Ne(α,γ) 26 Mg reaction rates using two different codes: the stellar models computed with the MESA code [34] presented by Battino et al [35] and the NEWTON code [4] presented by Trippella et al [36]. In Figures 4 and 5 we compare our results concerning Rb abundances as a function of the total s-process abundances observed through the spectroscopy of carbon stars [37,38] of initial metal content similar to our models (Z = 0.02 and Z=0.03).…”
Section: Impact For S-process Calculations a Main S-process Frmentioning
confidence: 99%
See 2 more Smart Citations
“…We re-computed the s-process nucleosynthesis for stellar models of 2 and 3M adopting our new evaluations for 22 Ne(α,n) 25 Mg and 22 Ne(α,γ) 26 Mg reaction rates using two different codes: the stellar models computed with the MESA code [34] presented by Battino et al [35] and the NEWTON code [4] presented by Trippella et al [36]. In Figures 4 and 5 we compare our results concerning Rb abundances as a function of the total s-process abundances observed through the spectroscopy of carbon stars [37,38] of initial metal content similar to our models (Z = 0.02 and Z=0.03).…”
Section: Impact For S-process Calculations a Main S-process Frmentioning
confidence: 99%
“…In Figures 4 and 5 we compare our results concerning Rb abundances as a function of the total s-process abundances observed through the spectroscopy of carbon stars [37,38] of initial metal content similar to our models (Z = 0.02 and Z=0.03). The M3.z3m2-hCBM model computed by Battino et al [35] are reported in Figure 4 while Figure 5 reports the comparison of the NEWTON code output with observations. In both cases, we include the results obtained adopting the reaction rates of Longland et al [5] and the rates evaluated in the present work without the Texas A&M results.…”
Section: Impact For S-process Calculations a Main S-process Frmentioning
confidence: 99%
See 1 more Smart Citation
“…We mention, in particular, those invoking diffusive processes (like thermohaline mixing, see [24]) and those based on more rapid, oscillatory or wave-like mechanisms. These last were soon revealed to be much more effective [25,26] and actually offer now the most widely debated scenarios. These same models also provide estimates for the extension of the 13 C reservoir (or pocket, as it is often called), where s-process nucleosynthesis occurs.…”
Section: O-isotopes In Al 2 O 3 Grainsmentioning
confidence: 99%
“…Discovery of anomalous abundances in certain isotopes that are daughters of radioactive nuclei involved several elements in the last decades of the 20th century [3,4]. Among other amazing findings, they led to the realization that the n-deficient isotope of Al, 26 Al, had been present in the ESS in a huge and uniform concentration ( 26 Al/ 27 Al 5 • 10 −5 ), sufficient to affect significantly, or even control, the heating of ancient materials, which induced the early differentiation of planetary embryos [5,6]. The presence in the ESS of live radioactive isotopes from various stellar sources (whose decay products, signalling their earlier existence, are often called fossil radioactivities) was since then the object of intense research [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%